2016
DOI: 10.4314/wsa.v42i3.07
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the challenges for groundwater governance during shale gas development in South Africa

Abstract: As a prelude to potential development of South Africa's shale gas resources, it is critical to develop and implement effective groundwater governance arrangements. Existing policies and plans were analysed to determine whether critical gaps or barriers exist that could potentially lead to impacts on groundwater systems. Ten high-priority governance challenges were identified: (a) defining relevant metrics for baseline groundwater quality and availability; (b) developing guidelines for shale gas resource licens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Sustainability 2018, 10, 164 2 of 23 economic research of considering the potential application of SG [7,25,[33][34][35][36], the environmental impact assessment in SG exploitation [21,[37][38][39][40][41][42][43][44][45][46][47][48] and many others. Anyway, with the evolution from initial exploitation to the more and more complicated development of SG, the diverse research of SG can be found in available literature during past decades.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sustainability 2018, 10, 164 2 of 23 economic research of considering the potential application of SG [7,25,[33][34][35][36], the environmental impact assessment in SG exploitation [21,[37][38][39][40][41][42][43][44][45][46][47][48] and many others. Anyway, with the evolution from initial exploitation to the more and more complicated development of SG, the diverse research of SG can be found in available literature during past decades.…”
Section: Methodsmentioning
confidence: 99%
“…Canada has also achieved a commercial development of SG and a number of countries and regions carried on the prospecting or developing work and related pilot test of SG [9][10][11][12]. Other countries, such as Poland [13,14], Australia [15,16], England [17][18][19], South Africa [20,21], Brazil [22], India [23], pay much attention to the search of SG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two companies that do this are the Canadian Association of Petroleum Producers (CAPP), which actively supports fracking fluid content disclosure (Ernst and Young, 2015;Ingelson & Hunter, 2014) and the International Petroleum Industry Environmental Conservation Association (2015), which supports voluntary sustainability disclosure. To encourage voluntary disclosure, the Fracfocus website (https://fracfocus.org/) stores voluntary disclosures on chemicals used during fracking (Maule, Makey, Benson, Burrows, & Scammell, 2013;Neville et al, 2017;Pietersen, Kanyerere, Levine, Matshini, & Beekman, 2016).…”
Section: Public Information Disclosurementioning
confidence: 99%
“…Rollbacks of regulations aimed at ensuring environmental protection are also problematic (Brady & Crannell, ). In South Africa it is especially difficult to enforce command‐and‐control regulations in the mining sector because the various departments have different mandates, limited regulatory oversight and monitoring, and a shortage of human and financial resources to enforce regulations (Centre for Environmental Rights, ; Pietersen et al, ). Compliance monitoring and enforcement of UOG extraction regulations by a specialized interdepartmental unit comprising the departments responsible for water, the environment and mineral extraction would therefore be useful for countries attempting to regulate UOG extraction.…”
Section: A Proposed Regulatory Framework For Uog Extractionmentioning
confidence: 99%